1997
DOI: 10.1590/s0074-02761997000800012
|View full text |Cite
|
Sign up to set email alerts
|

IL-5 and IL-5 receptor in asthma

Abstract: and a soluble isoform (αIL-5Rs). Cytokines such as IL-5 produce specific and non-specific cellular responses through specific cell membrane receptor mediated activation of intracellular signal transduction pathways which, to a large part, regulate gene expression. The major intracellular signal transduction mechanism is activation of non-receptor associated tyrosine kinases including JAK and MAP kinases which can then transduce signals via a novel family of transcriptional factors named signal transducers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 144 publications
0
45
0
1
Order By: Relevance
“…Such EOS recruited to the asthmatic airway exhibit increased ␣M␤2 expression compared with EOS in blood (78 -80). Activation of ␣M␤2 (45,77) and formation of podosomes of EOS (25), structures believed important in cell migration (70), are induced by exposure to IL-5, which is up-regulated in the blood and airway of human asthmatics (42,(81)(82)(83). In addition, the chemokines RANTES (regulated on activation, normal T-cell expressed and secreted), monocyte chemotactic protein-3, and complement activation factor-5 expose an activation-sensitive epitope of ␣M␤2 (84) and promote migration of blood EOS (84 -87).…”
Section: Discussionmentioning
confidence: 99%
“…Such EOS recruited to the asthmatic airway exhibit increased ␣M␤2 expression compared with EOS in blood (78 -80). Activation of ␣M␤2 (45,77) and formation of podosomes of EOS (25), structures believed important in cell migration (70), are induced by exposure to IL-5, which is up-regulated in the blood and airway of human asthmatics (42,(81)(82)(83). In addition, the chemokines RANTES (regulated on activation, normal T-cell expressed and secreted), monocyte chemotactic protein-3, and complement activation factor-5 expose an activation-sensitive epitope of ␣M␤2 (84) and promote migration of blood EOS (84 -87).…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial asthma is characterized by exaggerated agonist-induced bronchoconstriction, attenuated ␤-adrenoceptor-mediated airway relaxation and airway inflammation, the latter principally involving infiltration of the airways with T lymphocytes, mast cells, and eosinophils (1)(2)(3)(4)(5)(6)(7)(8)(25)(26)(27)(28). Although the mechanistic interplay between airway inflammation and the associated changes in ASM responsiveness remains to be fully characterized, the wealth of evidence accumulated to date suggests that the altered airway responsiveness in asthma is primarily attributed to the actions of various cytokines, which are primarily produced by infiltrating CD4 ϩ T lymphocytes expressing the Th2 profile of cytokine release (1-8, 27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…In many different studies, eosinophils are considered the main cells involved in the genesis of these diseases. 5,6 Thus, in these studies, we considered to be value any type of eosinophilic NSP, and there was no distinction among the studied cases. Kramer et al (2000) 17 suggested that the mechanisms involved in the genesis of eosinophilic polyposis, of allergic origin or not, are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Such cytokines, associated with eosinophils, acquire a key role in the pathophysiology of eosinophilic NSP. [2][3][4][5][6] The use of MMC is extremely important because it is an antineoblastic and antibiotic drug that acts as an alkylating agent, inhibiting DNA, protein synthesis and fibroblasts in cell cultures. MMC has been experimentally used in the prevention of stenosis in maxillary antrostomies, glaucoma surgery and pterygiums, in myringotomy and in laryngeal stenosis.…”
Section: Introductionmentioning
confidence: 99%